The Evaluation of Management Standards on Accreditation Results of PAUD Institutions in 2017 Year (Study of Accreditation Results Documents in BAP PAUD and PNF West Kalimantan) - Hamka Hamka; Wahyudi Wahyudi; M. Chiar (JETL (Journal of Education, Teaching and Learning), 2019)
The purpose of this study was to determine the results of accreditation on the standard aspects of PAUD management. This research method uses a documentary study method with a qualitative approach. This type of research in this study is a descriptive case study research. Based on the evaluation recapitulation of all aspects of the management standard that PAUD institutions on average do not yet have a work inspection and assessment document therefore it is a problem that the low achievement period of 8 standards in PAUD units that apply for accreditation in 2017 due to the low 2 aspects PAUD institutions have not yet been launched.